2006
DOI: 10.1103/physrevb.74.014405
|View full text |Cite
|
Sign up to set email alerts
|

Thermoinduced magnetization and uncompensated spins in antiferromagnetic nanoparticles

Abstract: We have investigated the combined effect of an uncompensated moment and the thermoinduced magnetization on the initial susceptibility of nanoparticles of antiferromagnetic materials. We find that for nanoparticles with small values of the anisotropy and exchange fields, the thermoinduced magnetization may be predominant at finite temperatures. In other cases the uncompensated moment may be predominant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 18 publications
4
58
0
Order By: Relevance
“…Nevertheless, the results shown in Fig.5(b) indicate that the α-dependent harmonic generation from the partially-aligned N 2 is strongly dominated with the HOMO of a single molecule. This result for N 2 reconciles with the previous theoretical 11,12) and experimental results. 6) For O 2 , η was estimated to be η = 0.48 at Δt = 5.70 ps for the S 1 peak and η = 0.23 at Δt = 5.91 ps for the S 2 minimum.…”
Section: O 2 Moleculessupporting
confidence: 82%
See 4 more Smart Citations
“…Nevertheless, the results shown in Fig.5(b) indicate that the α-dependent harmonic generation from the partially-aligned N 2 is strongly dominated with the HOMO of a single molecule. This result for N 2 reconciles with the previous theoretical 11,12) and experimental results. 6) For O 2 , η was estimated to be η = 0.48 at Δt = 5.70 ps for the S 1 peak and η = 0.23 at Δt = 5.91 ps for the S 2 minimum.…”
Section: O 2 Moleculessupporting
confidence: 82%
“…Theoretical studies have shown so far that the angle-dependent HHG from a single molecule is dominated by the HOMO. [11][12][13][14] The electron density distribution of the π g orbital of O 2 are quite different from that of the σ g of N 2 , and then the theory predicts that the angle-dependent HHG almost follows the electron distribution of the HOMO. However, the α-dependent harmonic signals observed for aligned O 2 molecules are very similar to those for N 2 , as seen in Figs.2 and 4.…”
Section: O 2 Moleculesmentioning
confidence: 99%
See 3 more Smart Citations